Biomechanical model analysis guide with open source software for educational purposes (LACCEI, 2024)
In Central America the implementation of biomechanical model analysis is well known to be a brand-new branch of science. The whole region has been working these studies from a qualitative point of view, which in most of the pathological cases is enough to diagnose or treat a patient. With the advances of computer vision, open code software, and interest in the biomechanical studies, by use of the package OpenCap and OpenSim, the quantitative analytics of biomechanical movements where successfully withdrawn. The combination of both software and their respective information outputs could allow theoretically a therapist to analyze deeply a pathology looking for differences in the movement ranges of any limb as OpenCap is capable of detecting. The objective of this research is to create a laboratory guide for the Biomechanics course of the Universidad Tecnologica Centroamericana UNITEC for the biomedical engineering degree. This software proved to be a versatile tool with a friendly interface for new users, especially students. Working along with OpenSim a complete biomechanical analysis of a specific patient can be generated. This analysis can help in several areas, for example, prothesis design and adaptation.